Immunohistochemical Expression of the Pluripotency Factor OCT4 in Canine Mast Cell Tumours - Vargas, T. H. M. (2015)
Cancer stem cells (CSCs) are related to malignancy and resistance to chemotherapy in several tumours. OCT4 is a 'pluripotency factor' that is expressed by these cells. The aim of the present study was to investigate OCT4 expression in canine cutaneous mast cell tumours (MCTs) by means of immunohistochemistry. Twenty-eight cases were evaluated and showed variable immunolabelling patterns. The dogs were treated by surgery alone and followed up for a minimum of 180 days. No significant difference was found between histopathological grades and similar results were obtained for mortality due to the disease and post-surgical survival. These preliminary results suggest that OCT4 expression is not a precise prognostic indicator for canine MCT. (C) 2015 Elsevier Ltd. All rights reserved.